Petunjuk adanya Reaktifasi Sesar Di Sekitar Aliran Sungai Opak, Perbukitan Jiwo Dan sisi Utara Kaki Pegunungan Selatan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Normal fault along Opak River and burial normal fault by alluvium along eastern Bayat to southern Prambanan have not been known whether they are produced by reactivation of old faults or not. This study intends to explain in term of their genesis. This study emphasizes on structural field data, especially minor structures observed on outcrops along Opak River, Jiwo Hills and northern foot of Southern Mountains. Tectonic principal stress forming the faults can be obtained by the help of computer. Possibility of the occurrence of the reactivation faults are interpreted from the trend of the principal stress forming the faults and faults data in field. Normal fault along Opak River was formed by reactivation of strike slip fault along this river. Tectonic stresses the normal fault and also form normal faults near Parangtritis. Reactivation of northeast-southwest strike slip fault become normal fault also can be observed at Kalinampu near Bayat (KB 1). Based on several tensional stress trend (a. 3) near Bayat, it can be explained that the burial normal fault at southern Bayat is controlled by reactivation of old fault or fractures.